Optimization of the CIP system enzyme stage for effluent reduction - Silva, Lucas Donizete; Gedraite, Rubens (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
Milk is one of the main foods and possesses considerable nutritional richness. In this sense, the consumption of industrialized food products has increased significantly and with this it is important to know and improve the processes of hygiene of the industry. Clean in Place (CIP) is a useful technology for cleaning equipment and pipes because it avoids dismantling and is made up of several steps, such as cleaning with alkaline detergent, rinsing, applying acid, rinse, sanitize and rinse. The objective of this work was to evaluate the water consumption and the consequent generation of effluent in the alkaline detergent rinsing stage using constant flow and pulsed flow rates and also to propose an optimal configuration of the pulsed flow to minimize the consumption of water and effluent generated. The tests were conducted in a CIP system prototype and executed based on a central composite planning (CCP) changing the variables amplitude, period and duration of the high part. The response surface technique was used to evaluate the effects of each variable on water consumption. It was verified that there is an optimum condition for the operation of the rinse in pulsed form with amplitude 1.5 L / min, period 138 seconds and duration of the high part of 53 seconds. In addition, it has been found that the rinse with pulsed flow produces an economy of approximately 14.52% in relation to the constant flow operation.